Indigenous People of Costa Rica and the Construction of its Imaginary from the Perspective of the Social Studies Curriculum: The Maleku Case - Naranjo Segura, Juan Carlos (2023)
This article summarizes the findings of the final graduation project, which aimed to analyze the dynamics of the official curriculum within the Social Studies program and its role in constructing imagery about indigenous peoples of Costa Rica, in contrast to the reality of these communities and their self-perception. The Maleku group was used as a reference, as well as the representations of ninth-grade students at the Colegio Técnico Profesional (CTP), in Zarcero, about these ethnic groups. The study considered aspects such as the economy, culture, daily life, and even myths and realities. The methodology was qualitative, using techniques such as life stories, semi-structured interviews, qualitative questionnaires, content analysis, and group interviews. It was determined that the program does not create stereotypes, but reproduces them. Furthermore, the opinions and assessments made by Maleku indigenous peoples about their reality break those stereotypes reproduced in the curriculum.